Habitat use and vestibular system's dimensions in lacertid lizards. Issue 1 (17th April 2019) - Vasilopoulou‐Kampitsi, Menelia; Goyens, Jana; Baeckens, Simon; Van Damme, Raoul; Aerts, Peter
Abstract : The vestibular system is crucial for movement control during locomotion. As the dimensions of the vestibular system determine the fluid dynamics of the endolymph and, as such, the system's function, we investigate the interaction between vestibular system size, head size and microhabitat use in lizards. We grouped 24 lacertid species in three microhabitat types, we acquired three‐dimensional models of the bony vestibular systems using micro‐computer tomography scanning, and we performed linear and surface measurements. All vestibular measurements scale with a negative allometry with head size, suggesting that smaller heads house disproportionally large ears. As the sensitivity of the vestibular system is positively related to size, a sufficiently large vestibular system in small‐headed animals may meet the sensitivity demands during challenged locomotion. We also found that the microhabitat affects the locomotor dynamics: lizards inhabiting open microhabitats run at higher dimensionless speeds. On the other hand, no statistical relationship exists between dimensionless speed and the vestibular system dimensions. Hence, if the vestibular size would differ between microhabitats, this would be a direct effect (i.e. imposed, for instance, by requirements for manoeuvring, balance control, etc.), rather than depending on the lizards' intrinsic running speed. However, we found no effect of the microhabitat on the allometric relationship between head and vestibular system size. The finding that microhabitat is not reflected in the vestibular system size (hence sensitivity) of the lacertids in this study is possibly due to spatial constraints of the skull.